(untitled) (Shaheed Smriti Journal, 2025)
This qualitative research examined the factors that shape employee motivation and how these factors influence job performance in agro-based firms operating in Ratnanagar Municipality, Chitwan, Nepal. Data were gathered through semi-structured interviews, focus group discussions, and on-site observations involving 30 employees and managers from three agro enterprises. The study explored both internal and external sources of motivation and how they affect employees’ performance, commitment, and intention to remain with their organizations. The findings indicate that recognition, purposeful work, supportive leadership, job security, fair compensation, and opportunities for personal and professional development play a significant role in motivating employees. Participants generally viewed intrinsic factors—particularly recognition and opportunities for growth—as having a stronger influence on effort, creativity, and dedication, while extrinsic factors such as salary and job stability were seen as essential for maintaining minimum levels of engagement. The study highlights the importance of adopting comprehensive human resource practices that reflect local cultural and economic realities. By offering qualitative evidence from Nepal’s agribusiness sector, the research adds context-specific insights to motivation theory and provides practical guidance for managers seeking to improve employee engagement and performance.